The Influence of YouTube Gamer Videos on Noun Vocabulary Acquisition Among Elementary School Children - Putri, Asyitunisah Adhitama Eka; Yani, Juli; Goziyah, Goziyah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to explore the influence of gamer videos on YouTube on the acquisition of noun vocabulary among elementary school children. Using a qualitative approach, the study examines how children's interaction with gaming video content affects their vocabulary development. Data were collected through in-depth interviews with 5 children, participatory observation, and video transcript analysis. The results indicate that children who regularly watch gamer videos show significant improvement in their understanding and use of new noun vocabulary. These findings highlight the potential of digital media as a language learning tool, emphasizing the importance of appropriate content supervision.